INTELLIGENT SYSTEMS FOR FORMING PROJECT TEAMS IN SAFETY-ORIENTED SYSTEMS - Balash, Liliya; Sodoma, Ruslana; Kovalchuk, Oleh (INNOVATIVE TECHNOLOGIES AND SCIENTIFIC SOLUTIONS FOR INDUSTRIES, 2023)
Human security project teams are formed in higher education institutions that train qualified civil protection specialists. One of the tasks is to increase the efficiency of forming SOS project teams by HR services, as well as to improve the recruitment and selection procedure using modern information technologies. Developing human resources, improving the quality of higher education for its applicants. Information systems provide high speed data processing, information search, recruitment optimization and candidate analysis. Automation of HR processes helps to reduce the labor intensity and resource costs of tasks. New models, methods, and technologies for processing materials and information about applicants for the purpose of evaluating them for further involvement in the SOS project will contribute to the sustainable development of the organization. The subject of the study is models for automating the selection of personnel in safety-oriented systems with their subsequent formation into project teams of the civil protection service and law enforcement agencies. One of the components of human resource management is the implementation of a subsystem for the assessment and selection of human resources, the initial elements of which are the basis for making personnel decisions on the formation of project teams. The purpose of the study is to formalize the criteria for selecting candidates to reduce the subjectivity of the assessment; optimize and automate the selection process, design expert decision support systems for HR. The article sets the following tasks: to design an information system for the formation of project teams in safety-oriented systems, taking into account the parameters of personal human qualities and professional skills of candidates using information expert systems. To improve the quantitative assessment and qualitative indicators of applicants, it is advisable to formalize the criteria and their weighting coefficients using the theory of qualimetrics and personnel assessment methods. The following research methods were used: system analysis, empirical methods, and project management methodology. The following results have been obtained: a model-scheme of an iterative approach to the development of an information system for human resource management for higher education institutions, taking into account specific learning conditions, has been developed. Conclusions. The methods of evaluation and selection of human resources, as well as the criteria for their selection in complex socio-technical systems are analyzed. The possibilities of automating HR processes and integrating an information system to support the formation of project teams in a safety-oriented system are considered. description of the life cycle of complex systems of a safety-oriented system, namely, the life cycle of such complex socio-technical systems is described, taking into account their characteristics and environment.